Mass transfer of organic substances in supercritical carbon dioxide - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Neukam, Johannes; Bielke, Thorsten; Delgado, Antonio; Nercissian, Vanusch; Berger, Andreas (Journal of Physics : Conference Series, 2011)
In this work special attention is paid on the direct visualization of the diffusion process of oil droplets in supercritical carbon dioxide as well as better characterization of the process by quantitatively evaluating the important parameter - the diffusion coefficients obtained with a shearing interferometer. Experiments are also to be carried out under microgravity to improve the experiment condition where the influence of gravity-driven convection that usually dominates the transport process is minimized.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.masstr_3

Untersuchungen zum Stofftransport ausgewählter Substanzen in überkritischem Kohlendioxid mittels Shearing-Intereferometrie - Hu, Miao; Benning, Rainer; Ertunc, Özgür; Bielke, Thorsten; Delgado, Antonio; Neukam, Johannes; Nercissian, Vanusch; Berger, Andreas (Proceedings der 19. GALA-Fachtagung "Lasermethoden in der Strömungsmesstechnik", 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.ITC.stmmec.unters